Change in gender relations: managerial and transformative approaches of gender mainstreaming in agriculture - Tegbaru, A.; Fitzsimons, J.; Gurung, B.; Odame, H.H. (2010)
This paper explores the managerial and transformative approaches to gender mainstreaming in order to draw a more comprehensive understanding of how institutional and behavioural change processes occur with regard to gender equality. Drawing from the managerial and efficiency path, and planning tools used in implementing a project in Northern Nigeria, Promoting Sustainable Agriculture in Borno State or PROSAB, and by exploring largely unintended/unforeseen consequences of project actions, the paper argues that change in gender relations should be viewed not as outcome of technology transfer following a simple input-output model conceptualised largely in linear terms, but rather as a complex social phenomenon based on people’s interests, motivations, relationships, and innovative actions that are embedded in their historical and cultural situations. It suggests that the managerial and efficiency approaches are insufficient to encourage change in gender relations. Drawing from the case of PROSAB, the paper underlines the importance of a transformative approach that understands change processes in gender relations and success in women empowerment, which are influenced by the interplay of multiple factors that are not project controlled.